دور بعض الأفعال المنظمية في إدارة الوقت دراسة مسحية في عينة من المكتبات الجامعية في بغداد - الكبيسي صلاح الدين عواد; الجنابي سامرة احمد (Journal of Economics and Administrative Sciences, 2010)
The organizations recognize what the effective role of time management in achieving competitive advantage and success. But the effectiveness depends on integrating some organization actions which perspective are relating with it by significance relations and high affect. From this the research problem is arising، which descripe the recognizing of libraries managers for the role of some organizational actions. The samples from (40) libraries managers are chosen. The major results: these organizational actions are related and affected on the time management if integrated with one anothers more than if related in separate.